Manual of Public Administration in Argentina: Nation, Provinces, and Municipalities Edited by Juan Manuel Abal Medina and Horacio Cao - Bizarro, Valeria (Revista del CLAD Reforma y Democracia, 2025)
The Manual of Public Administration in Argentina: Nation, Provinces, and Municipalities, edited by Juan Manuel Abal Medina and Horacio Cao, is a key reference work for studying statehood through a federal lens. Published by the National University of Córdoba and the National University of Quilmes, it offers a comprehensive and comparative approach to national, provincial, and municipal levels of government. Its structure weaves together historical, constitutional, organizational, budgetary, and political-institutional dimensions, ensuring analytical coherence and methodological rigor. Each chapter, written by experts in government levels and intergovernmental relations, combines theory with updated empirical evidence, providing data on public employment, budgets, and public policies. The foreword by Oscar Oszlack highlights the manual’s contribution to reclaiming public administration as a distinct field of knowledge.